Nexus Between Economic Growth, Health, and Education in Pakistan: An ARDL Bound Testing Approach - Javed, Rimsha (International Journal of Economics and Financial Issues, 2021)
The main theme of this research is to determine the ramification of investment on the human that is health and education on economic activities in Pakistan. The nature of figurative data is time series that is used for statistical measures which is spanning from 1971-2017. The econometric technique used to gauge the linkages between the above variable is the ARDL approach. Another technique called the Granger Causality has been employed to determine the regulation of effect in variables under consideration. While two diagnostic measures were used. The results depict that better health has implications on GDP while there exists convergence from short period to longer span. While empirical results show that economic growth gets more affected by education in a shorter period as compared to a longer period. RAMSEY RESET test revealed that this model was free of any misspecification and recursive measure also confirmed the same for this study. Keywords: Economic Growth, Health, Education, ARDL, Pakistan JEL Classifications: I10, I15, I25. DOI: https://doi.org/10.32479/ijefi.12535